Editing of Chloroplast rps14 by PPR Editing Factor EMB2261 Is Essential for Arabidopsis Development - Sun, Yueming K.; Gutmann, Bernard; Yap, Aaron; Kindgren, Peter; Small, Ian (Frontiers in Plant Science, 2018)
RNA editing in plastids is known to be required for embryogenesis, but no single editing event had been shown to be essential. We show that the emb2261-2 mutation is lethal through a failure to express an editing factor that specifically recognizes the rps14-2 site. EMB2261 was predicted to bind the cis-element upstream of the rps14-2 site and genetic complementation with promoters of different strength followed by RNA-seq analysis was conducted to test the correlation between rps14-2 editing and EMB2261 expression. Rps14-2 is the only editing event in Arabidopsis chloroplasts that correlates with EMB2261 expression. Sequence divergence between the cis-element and the EMB2261 protein sequence in plants where rps14-2 editing is not required adds support to the association between them. We conclude that EMB2261 is the specificity factor for rps14-2 editing. This editing event converts P51 in Rps14 to L51, which is conserved among species lacking RNA editing, implying the importance of the editing event to Rps14 function. Rps14 is an essential ribosomal subunit for plastid translation, which, in turn, is essential for Arabidopsis embryogenesis.